Pemanfaatan Digital Branding UMKM Barongan Wisanggeni Guna Mendukung Tercapainya SDGs Desa Kewirausahaan - Negara, Muhammad Handito Perwira; Sholihah, Dewi Deniaty (CV. ITTC INDONESIA, 2023)
SMALL AND MEDIUM ENTERPRISES (UMKM) play a crucial role in creating jobs, distributing income, and supporting economic growth. The mastery of information and communication technology provides opportunities for UMKM through social media platforms like YouTube and Instagram. Digital strength and effective branding strategies are essential for UMKM Barongan Wisanggeni Art Gallery to face technological advancements and meet the demands of sophisticated consumers. In the context of sustainable development, Kelompok KKNT 27 supports the Sustainable Development Goals (SDGS) of Entrepreneurship Village by empowering the local economy and creating a competitive environment for future generations. The objective of this initiative is to provide education on branding for entrepreneurs and enhance the target market through product branding. The target beneficiaries are the general public in Ngadirejo Village, Blitar City. The implementation of the SDGS of Entrepreneurship Village and digital branding is expected to achieve economic independence and support sustainable development. This activity represents a tangible step in supporting UMKM and the local economy towards inclusive development.